2023
DOI: 10.36689/uhk/hed/2023-01-061
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Forecasting Analysis of the Development of Technical Infrastructure in the Vicinity of Airports in Poland

Abstract: Research in the field of infrastructural development has attracted quite a lot of interest. A significant part of them concerns the regions of the European Union. However, in the European literature definitely lacks positions in which technical infrastructure is analyzed in catchment areas of airports in Poland. The lack of literature items concerning the infrastructural development of districts located in the overlapping areas of influence of at least two ports is particularly noticeable. The author decided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…During the research, a statistical assessment was made of the level of infrastructure development in counties located in the three studied isochrones. In the last et al (2018) or Surówka (2023) or Kałuża-Jurczyńska et al (2021)). During the analysis of the isochrones covered by the study, it was observed, among other things, that the studied units are characterized by statistically significant differences.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…During the research, a statistical assessment was made of the level of infrastructure development in counties located in the three studied isochrones. In the last et al (2018) or Surówka (2023) or Kałuża-Jurczyńska et al (2021)). During the analysis of the isochrones covered by the study, it was observed, among other things, that the studied units are characterized by statistically significant differences.…”
Section: Discussionmentioning
confidence: 98%
“…Many methods are used for forecasting. In the practical part, the medium-term rate of change method was used (Surówka, 2023). Forecasts using this method are made using the following formulas:…”
Section: Forecasting As a Research Toolmentioning
confidence: 99%
See 2 more Smart Citations